Equality of the sexes and gender differences in competition: evidence from three traditional societies [supplementary materials] - Klonner, Stefan (Universität, 2020)
Can gender-balanced social norms mitigate the gender differences in competitiveness that are observed in traditional patriarchic as well as in mode...
Gesehen am 09.03.2020
Keywords: Forschungsdaten; Datenbank